Analysis of Students' Difficulties in Solving Story Problems in Comparative Material for Class VII SMP - Tobing, Ernita Br Lumban; Anim, Anim; Sitorus, Marudut (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The poor daily scores of pupils resulting from their struggles with mathematical problem solving served as the impetus for this study. Finding out how difficult it is for students to solve narrative issues using comparison material is the goal of this study, which also aims to offer alternate options. This study was carried by utilizing a qualitative descriptive technique at UPTD SMP Negeri 4 Kisaran school. Purposive sampling procedures were used in this study, which included 31 participants from the entire population of class VII students at UPTD SMP Negeri 4 Kisaran, or up to 210 persons. The research was condcted during the odd semester of the 2022–2023 academic year. The study's data came from test findings. There are five essay-style test questions in this course that are all about comparative materials. Selecting and using the appropriate formula to solve arithmetic problems is the most common sort of difficulty that students have when working on comparison material narrative questions (53%). Based on the data processing findings, it was determined that class VII UPTD SMP Negeri 4 Kisaran students' level of difficulty in completing narrative problems met the